2017
DOI: 10.20868/bma.2017.1.3519
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of BIM in Spanish construction industry = Implementación BIM en la industria española de la construcción

Abstract: The Spanish construction industry has been subject to EU Directive 2014/24/UE. This directive allows member states to encourage, specify and even require the use of Building Information Modeling (BIM) in construction projects financed by EU public funds as of 2016. The QBIMInvest Project (supported by the Universidad Europea de Madrid) has conducted a survey, which is the subject of this article, on the implementation of Building Information Modeling in the Spanish AEC industry. This research uses 548 response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Moreover, all the participating AEC companies listed "the cost of training", "the cost of software", and "huge BIM upfront investment" as among the top five barriers in implementing BIM. This is consistent with other similar studies that have identified these barriers as either significant or normal barriers to BIM implementation [28,32,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. In Jordan, these results are likely because many Jordanian companies work on governmentfunded projects, while others work on private projects funded by the owner, who is also making decisions regarding the project.…”
Section: Discussion and Comparison Of The Results With Other Studiessupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, all the participating AEC companies listed "the cost of training", "the cost of software", and "huge BIM upfront investment" as among the top five barriers in implementing BIM. This is consistent with other similar studies that have identified these barriers as either significant or normal barriers to BIM implementation [28,32,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. In Jordan, these results are likely because many Jordanian companies work on governmentfunded projects, while others work on private projects funded by the owner, who is also making decisions regarding the project.…”
Section: Discussion and Comparison Of The Results With Other Studiessupporting
confidence: 86%
“…On the other hand, despite knowing of BIM importance, the most common reason for some AEC companies in Spain not to use BIM is related to the expense of software, owner refusal, a lack of qualified people, and company unreadiness to start using it [32]. A survey of Ireland enterprise agreed with these results, and added the unavailability of standard tools and some problems related to data ownership [33].…”
Section: Bim Barriersmentioning
confidence: 99%
“…BIM is an effective tool for building performance analysis. BIM integrates project systems, building information and the project management team to provide safe and convenient data transmission and storage methods, which improves the efficiency of green evaluation [16,17]. However, the research of green BIM technology in the design stage is not sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…It is being used mainly at this stage for design and modelling, with fewer using BIM in the construction stage or after. 62 Spain is part of the European Union (EU) and all projects underwritten with EU public funds are already mandated to establish and maintain a BIM working environment. Beyond the national level as per this policy, several regional governments in Spain have decided to implement the same type of mandate and require BIM methodology for their publicly funded projects.…”
Section: Europementioning
confidence: 99%